2023
DOI: 10.12765/cpos-2023-04
|View full text |Cite
|
Sign up to set email alerts
|

Biases in Assertions of Self-Rated Health

Abstract: Comparative analyses frequently examine respondents’ self-rated health (SRH), assuming that it is a valid and comparable measure of generic health. However, given SRH’s vagueness, this assumption is questionable due to (1) manifold non-health influences, such as personal characteristics including optimism, interviewer effects on the rating, and cultural contexts, as well as (2) potential gender, age- or country-specific expectations for one’s health or frames of reference. Conceptually, two major components of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The non-health variables used in these analyses were as follows (the distributions of these variables are shown in Table S 3 in the appendix): Education : According to prior research, respondents with higher formal education appear to rate similar health states more positively [ 19 ], possibly due to their ability to use their resources to alleviate negative effects of health problems. However, other research only found this effect for male respondents [ 8 ], highlighting the necessity of separate analyses by gender. In the DEAS data, education was available in the form of three groups that are based on the International Standard Classification of Education (ISCED) representing low (ISCED 0–2), medium (ISCED 3–4), and high education (ISCED 5–6) [ 20 ].…”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…The non-health variables used in these analyses were as follows (the distributions of these variables are shown in Table S 3 in the appendix): Education : According to prior research, respondents with higher formal education appear to rate similar health states more positively [ 19 ], possibly due to their ability to use their resources to alleviate negative effects of health problems. However, other research only found this effect for male respondents [ 8 ], highlighting the necessity of separate analyses by gender. In the DEAS data, education was available in the form of three groups that are based on the International Standard Classification of Education (ISCED) representing low (ISCED 0–2), medium (ISCED 3–4), and high education (ISCED 5–6) [ 20 ].…”
Section: Methodsmentioning
confidence: 89%
“…As the final part of this paper’s analyses, I analyzed the influence of further non-health biases on each health measure by employing a multi-step analytic approach already described in greater detail elsewhere [ 8 ]. In short, the first step of this approach consists of using a linear regression model explaining the generic health measure in question with as many health indicators as available in the data set.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-rated health may be subject to varying perceptions based on individual characteristics such as culture, age, and gender. Future research could benefit from incorporating objective health measures to validate self-rated health assessments, as proposed by Lazarevič 36 . Similarly, the perception of social support can also be influenced by several factors, including the quality and closeness of interpersonal relationships, the availability and accessibility of social resources, and the person’s ability to seek and use available support.…”
Section: Discussionmentioning
confidence: 99%